Cardiorespiratory fitness in stroke patients with different activities of daily living levels: a cross-sectional study - Dongxia Li; Mingchao Zhou; Fubing Zha; Jianjun Long; Yulong Wang (Scientific Reports)
Abstract Understanding the relationship between cardiorespiratory function (CRF) and activities of daily living (ADL) in stroke patients is essential for improving rehabilitation outcomes. A total of 153 participants were enrolled in this study. Cardiopulmonary exercise was tested at admission. A multivariable linear regression was performed to identify variables associated with peak oxygen uptake (VO2peak). Participants with low ADL exhibited poorer responses to exercise than those with high ADL levels. After adjusting for confounders, the multiple linear regression analysis showed that albumin-to-globulin ratio (AGR) and left ventricular posterior wall thickness (LVPW) were significantly associated with VO2peak in all patients. In the low ADL subgroup, the positive association between AGR and VO2peak was consistent. Conversely, the negative association between LVPW and VO2peak was uncertain. Otherwise, no significant association were found between AGR, LVPW, and VO2peak in the high ADL subgroup. This study provides new insights into the relationship between CRF and ADL in stroke patients, with a focus on ARG and LVPW. Future studies with larger sample sizes are needed to further explore the role of AGR and LVPW in improving the CRF in stroke patients.